Pengaruh Latihan Variasi terhadap Pukulan Long Forehand Bulutangkis pada Pemain PB Bungo Badminton Club - Arif Rahman; Ikhsan Maulana Putra; Titis Wulandari (CV. Master Literasi Indonesia, 2025)
This research is motivated by the low ability in executing long forehand strokes among PB Bungo Badminton Club athletes aged 12–18 years, as indicated by poor accuracy, power, and reach to the back area of the opponent's court. The study aims to determine the effect of variational training on the long forehand stroke ability in badminton. This is a quantitative study using a quasi-experimental method with a one-group pretest-posttest design. The population consisted of 20 athletes, with a sample of 15 male athletes selected through purposive sampling. The research was conducted at Panam Hall, Bungo Regency, in juni and July 2025, over a period of 6 weeks with a total of 16 training sessions (3 times per week). The instrument used was a long forehand stroke test consisting of 20 attempts, assessed according to a standardized scoring rubric. Based on the results of the t-test analysis, the long forehand stroke ability increased from an average pretest score of 29.13 to 58.73 in the posttest, with a difference of 29.6 points. The distribution of posttest results showed that 8 athletes (53.33%) were in the “Very Poor” category, 4 athletes (26.66%) in the “Poor” category, 2 athletes (13.33%) in the “Fair” category, and 1 athlete (6.66%) had not yet met the assessment criteria. Based on the data analysis using the t-test, the obtained t-value was 11.385, which is greater than the t-table value of 1.761. This indicates that variation training has a significant effect on the long forehand stroke in badminton players at PB BBC.